2004
DOI: 10.1016/j.ejheart.2003.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Desmin‐free cardiomyocytes and myocardial dysfunction in end stage heart failure

Abstract: Our aim was to evaluate the desmin content in the myocardial tissue of patients with end-stage heart failure of ischaemic origin and to assess its role on cardiac function. We studied 18 explanted hearts from patients transplanted for end-stage heart failure due to ischaemic cardiomyopathy (ICM). Control myocardial tissue was obtained from the cardiac biopsies of six women with breast cancer taken prior to commencing chemotherapy with anthracyclines, four male donors for heart transplantation and two autoptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 34 publications
5
23
1
2
Order By: Relevance
“…For example, some cardiomyocytes were completely devoid of desmin staining, whereas neighboring cardiomyocytes had intact desmin staining along Z lines. A similar desmin staining pattern has been previously described by Di Somma and coworkers (13) in humans with end-stage heart failure due to ischemic cardiomyopathy. Quan-…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…For example, some cardiomyocytes were completely devoid of desmin staining, whereas neighboring cardiomyocytes had intact desmin staining along Z lines. A similar desmin staining pattern has been previously described by Di Somma and coworkers (13) in humans with end-stage heart failure due to ischemic cardiomyopathy. Quan-…”
Section: Resultssupporting
confidence: 52%
“…In fact, some cardiomyocytes exhibit a near-complete loss of desmin in conjunction with decreased mitochondrial complex IV staining. A patchy, near-total loss of desmin in cardiomyocytes has also been reported in patients with idiopathic dilated cardiomyopathy (13). Disorganization of desmin and mitochondria functional complexes with myofibrils and the sarcoplasmic reticulum have been shown to be present before the onset of cardiac and skeletal muscle failure (3, 6, 24 -28, 36, 38).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This may be a result of damage of the desmin network in cardiomyocytes. This result is at variance with that reported by (Somma et al, 2004) who reported that a significant decrease in the amount of desmin in diseased myocardial compared to normal tissue.…”
Section: Discussioncontrasting
confidence: 57%
“…We have reported desmin breakdown and increased cardiomyocyte oxidative stress in rats with the primary volume overload of aortocaval fistula and in isolated cardiomyocytes subjected to cyclical stretch (25). Other studies have recently shown a similar disruption and patchy loss of desmin in left ventricles of patients with ischemic cardiomyopathy that is related to the extent of LV dysfunction and poor prognosis (26,27). The relation of desmin breakdown to long-term survival and to severity of LV dysfunction in human heart failure provides compelling evidence for a non-genetic cause of desmin degradation in the pathophysiology of LV functional deterioration in human heart failure and our MR patients.…”
Section: Discussionmentioning
confidence: 67%